2015
DOI: 10.4236/wjcd.2015.51002
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Risk Factors Attributed to Coronary Artery Disease in Women Attended Health Services in Gaza-Palestine Observational Study

Abstract: Coronary artery disease (CAD) is the leading cause of death in both sexes worldwide, and becomes number one killer in women due to many factors including increase in traditional risk factors, delays in apparition of symptoms, under estimation of diagnosis test and treatment. Our study aims to identify risk factors for coronary artery disease among women with chest pain underwent coronary angiography during years (2010-2013) in cardiology center. The study design is an observational among 688 women-aged 32 -96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Based on the results, more patients had DM in ≥45 years old compared to <45 group. Previous studies showed that DM entails a 5-fold increase in the risk of CAD for females while for diabetic males the augment is 2-fold [1]. It should be emphasized that the complex role of DM in the young patients should be better elucidated in the future large investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, more patients had DM in ≥45 years old compared to <45 group. Previous studies showed that DM entails a 5-fold increase in the risk of CAD for females while for diabetic males the augment is 2-fold [1]. It should be emphasized that the complex role of DM in the young patients should be better elucidated in the future large investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The AIP of male and female in this study was observed to be significantly increased when compared with baseline value (Table 7) similar to other studies. 25,26 AIP values of-0.3 to 0.1 are associated with low, 0.1 to .0.24 with medium and ≥0.24 with high cardiovascular risk. AIP has a better prediction of coronary artery disease than individual lipids, and/or TC/HDL-c, LDL-c/HDL-c ratios.…”
Section: Discussionmentioning
confidence: 94%
“…26 In our study, majority of patients were in the age group 50-60 years and in the postmenopausal groups which is a similar finding as in many studies in the past. 12,27 This indicates most of the patients with older age are more likely to have anginal symptoms and hence likely to under go CAG. Among three groups, the one with age >65 years has maximum proportion of patients with >/=3 risk factors, a similar finding found in one study done in Indian females.…”
Section: Discussionmentioning
confidence: 99%